T Cell-Derived IL-17A Induces Vascular Dysfunction via Perivascular Fibrosis Formation and Dysregulation of ⋅NO/cGMP Signaling. (18th July 2019) - Schüler, Rebecca; Efentakis, Panagiotis; Wild, Johannes; Lagrange, Jérémy; Garlapati, Venkata; Molitor, Michael; Kossmann, Sabine; Oelze, Matthias; Stamm, Paul; Li, Huige; Schäfer, Katrin; Münzel, Thomas; et al.
Abstract : Aims . The neutrophil recruiting cytokine Interleukin-17A (IL-17A) is a key component in vascular dysfunction and arterial hypertension. Moreover, IL-17A has a central role for the vascular infiltration of myeloid cells into the arterial wall in Angiotensin II-induced vascular inflammation. The intention of our study was to analyze the impact of T cell-derived IL-17A on hypertension, vascular function, and inflammation. Methods and Results . Chronic IL-17A overexpression in T cells (CD4-IL-17A ind/+ mice) resulted in elevated reactive oxygen species in the peripheral blood and a significant vascular dysfunction compared to control mice. The vascular dysfunction seen in the CD4-IL-17A ind/+ mice was only accompanied by a modest and nonsignificant accumulation of inflammatory cells within the vessel wall. Therefore, infiltrating myeloid cells did not serve as an explanation of the vascular dysfunction seen in a chronic IL-17A-driven mouse model. In addition to vascular dysfunction, CD4-IL-17A ind/+ mice displayed vascular fibrosis with highly proliferative fibroblasts. This fibroblast proliferation was induced by exposure to IL-17A as confirmed by in vitro experiments with primary murine fibroblastic cells. We also found that the ⋅ NO/cGMP pathway was downregulated in the vasculature of the CD4-IL-17A ind/+ mice, while levels of protein tyrosine kinase 2 (PYK2), an oxidative stress-triggered process associated with T cell activation, were upregulated in the perivascular fat tissue (PVAT). Conclusions . Our data demonstrate that T cell-derived IL-17A elicits vascular dysfunction by mediating proliferation of fibroblasts and subsequent vascular fibrosis associated with PYK2 upregulation.